PENGEMBANGAN BAHAN AJAR BERBASIS PROBLEM BASED LEARNING BERBANTUAN POWERPOINT VIDEO PADA MATERI SPLDV UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Riosanddy Nazaretha; Heris Hendriana; Luvy Sylviana Zanthy (IKIP Siliwangi, 2022)
The purpose of this Study was to produce teaching materials based on Problem Based Learning's Approach with a valid, effective and practical using powerpoint video to enhance problem solving mathematics abilities. The study was conducted in three public Junior High Schools at Empat Lawang District, South Sumatra. The research methode of this teaching materials development modified from the Borg & Gall's model. This study was conducted in class VIII consisting of 18 students as first trial sample, 28 students as second trial sample and 60 students as final sample. The instruments were: interview sheet, validation sheets, reading sheets, student responses, and problem solving tests. The result showed that: (1) 78.89% from main field testing students were good interpretations and 81.43% operational field testing students were very good interpretation, which means that the teaching material can be directly used without revision process; (2) at the phase of product testing showed that the development of teaching materials using powerpoint video was